Factors associated with major complications defined by Clavien–Dindo classification 3–5 after liver transplantation: a prospective multicenter cohort study - Sabate, Antoni; Caballero, Marta; Gutierrez, Rosa; Pérez, Lourdes; Vidal, Julia; Llaurado, Sandra; Hereu, Pilar; Peñafiel, Judith; Blasi, Annabel (Frontiers in Surgery, 2025)
BackgroundWe aimed to explore factors preoperative and intraoperative, associated with Clavien–Dindo classification 3–5 (CDC 3–5) after LT.MethodsSecondary analysis of multicenter prospective cohort data for 305 consecutive patients. European Clinical Trials Database -EudraCT 2018-002510-13. The primary outcome was the incidence of CDC 3–5 complications recorded during the ICU stay. We used a log-binomial regression model to evaluate associations.ResultsCardiac-death donors provided 30.16% of grafts. Vena cava preservation was performed in nearly all patients, and a temporary portacaval shunt was used in 41.91%. Intraoperative red blood cell (RBC) transfusion was required in 51.48%, and 27.37% required additional transfusions within 24 h of LT. CDC 3–5 status occurred in 97 patients (31.80%, 95% CI, 26.58%–37.03%). Thrombotic events occurred in 19 patients (6.25%): 6 in portal veins, 5 in hepatic arteries, 2 in mesenteric veins, and 6 in deep veins. Two patients were retransplanted. Twenty-two (7.21%) required reinterventions; 2 were retransplanted; and 20 (6.57%) were readmitted to the ICU. Adjusted relative risk (aRR) calculation found associations with a MELD score >23 (aRR, 1.92; 95% CI, 1.28–2.8), baseline hemoglobin concentration (aRR, 0.98; 95% CI, 0.97–0.99), zero RBC transfusion (aRR, 0.37; 95% CI, 0.28–0.72), an RBC transfusion cut point of >2.5 (aRR, 1.96; 95% CI, 1.29–2.96), PRS (aRR, 2.11; 95% CI, 1.43–3.10), and fibrinogen administration (aRR, 1.07; 95% CI, 1.05–1.09). We found no associations with temporary portocaval shunt (aRR, 1.02; 95% CI (0.7–1.48), cold and warm ischemia times or surgical time and intraoperative fluid administration.ConclusionWe conclude that PRS at reperfusion of the liver graft and the volume of RBCs transfused are the main modifiable factors that influence major complications reflected by CDC 3–5 status after LT.Clinical Trial Registrationhttps://clinicaltrials.gov/, identifier NCT04405518.